Influences of the switched-inductor and switched-capacitor blocks on the gain of an improved step-up converter - Ghaderı, Davood (Institute of Electrical and Electronics Engineers Inc., 2020)
The main concern in Photovoltaic (PV) panels is the generation of the limited values of the voltage. This voltage is not proper for grid-connected applications and in the first step, it should be increased. This is done by the application of a DC-DC boost converter. By enhancing the voltage level, the power transmission through the voltage will be possible and the efficiency of the converter circuit will be increased. This study presents a switched-capacitor (SC) and a switched-inductor (SI) block for applying in boost converter in order to obtain higher DC voltage gain. The main advantage of the converter is that it does not use the transformer and has a non-isolated structure. The charging of the input inductors will be done when the power switch is activated. In this time interval, the capacitors on the SC side are discharged by generating a serial connection. The discharging process for the inductors in the SI side is done for the deactivation time period of the switch and at the same time, the capacitors in the SC side are charged in parallel. The circuit states for obtaining the voltage gain are investigated and simulation results in MATLAB/SIMULINK are presented for stress evaluations across the power components. © 2020 Turkish Chambers of Electrical Engineers.
Anahtarlamalı indüktör ve Anahtarlamalı Kapasitör Bloklarının Geliştirilmiş Bir Yükseltici Dönüştürücünün Kazancı Üzerinde Etkileri
12th International Conference on Electrical and Electronics Engineering, ELECO 2020 -- 26 November 2020 through 28 November 2020 -- -- 166560
Keywords: [No Kerywords]